Risk prediction instrument for premature rupture of membranes based on clinical parameters and obstetric history - Rosyidah, Rafhani; Azizah, Nurul; Cholifah, Siti (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2025)
Background: Premature rupture of membranes is one of the most significant obstetric complications, with a direct impact on increasing the risk of infection, preterm labor, and perinatal mortality. In Indonesia, the main challenge in managing premature rupture of membranes is the late identification of at-risk pregnant women due to the unavailability of objective and practical screening instruments.Objective: This study aims to develop and test the validity of a clinical and obstetric history-based early rupture risk prediction instrument that can be widely applied in primary health care.Methods: The research design used a case control approach with a total of 450 respondents, consisting of case and control groups. Data were obtained from medical records and analyzed through chi-square test and logistic regression to identify significant risk factors. A score prediction model was then developed and validated using ROC curve, Youden index, and sensitivity-specificity analysis.Results: Four variables proved significant in the final model: age beyond 20-35 years, at-risk parity (primipara or grandemultipara), anemia, and fetal abnormality. The prediction score constructed based on these four factors had an Area Under the Curve value of 0.887, with a sensitivity of 82.4% and specificity of 84.8% at a cut-off point of >2.50. The overall accuracy of the model reached 0.86, indicating excellent classification performance.Conclusions: This score-based prediction model was shown to be valid and can be used as a practical screening tool to detect early risk of premature rupture of membranes. Its application is expected to strengthen efforts to prevent obstetric complications and improve the quality of maternal care in Indonesia